Bombesin-like peptides and their receptors: recent findings in pharmacology and physiology. Issue 1 (February 2015) - Guo, Man; Qu, Xiangping; Qin, Xiao-Qun
Abstract : Purpose of review: To highlight the research progress of roles of bombesin-like peptides and their receptors in pharmacology and physiology. Recent findings: Several new bombesin-derived radioactive or nonradioactive compounds were designed for the diagnosis and therapy of tumors that are overexpressing bombesin receptors. Both gastrin-releasing peptide receptor and neuromedin B receptor activation were shown to induce membrane depolarization and excite neurons in brain. Bombesin receptor subtype-3 was found to be downregulated in the muscle cells and myocytes from obese and type 2 diabetes patients, and its relevant cell signaling events in glucose homeostasis were also investigated. The molecular events triggered by bombesin receptors activation in different types of malignancies is being explored recently and new clues were provided for a better understanding of the biological roles of abnormal expression of bombesin receptors in tumors. Novel cross-talk between gastrin-releasing peptide receptor cell signaling and Sonic hedgehog pathways was identified in small-cell lung carcinoma. Summary: Increasing evidence shows bombesin-like peptides and their receptors play important roles in both physiological state and diseases. More specific and safe tumor targeting Bombesin derivatives are being developed for tumor diagnosis and therapy.